(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
There is a great specific positive contribution to the teaching of the law of the disciplines of Ethics, the humanistic values that the Encyclical Laudato Si proposes regarding an integral ecological in the latitude of its concepts, intergenerational equity, and other values imposed on the Sustainable Development Goals SDG (United Nations) and the discipline of Human Rights. However, it is presented as essential to develop practical training in all aspects related to the subject of Human Rights, Sustainable Development Goals, the concept of Integral Ecology and intergenerational equity, as well as the modification of the Study Programs to produce the expansion of the quantity hours to include these topics, since the interconnection between some of them is not detected in a significant percentage of the students.